Anisakis physeteris Baylis 1923 ... - Hernández-Orts, Jesús S.; Viola, M. Natalia Paso; García, Néstor A.; Crespo, Enrique A.; González, Raúl; García-Varela, Martín; Kuchta, Roman (Zenodo, 2015)
Anisakis physeteris (Baylis, 1923) Host: Physeter macrocephalus Linnaeus Site in host: stomach Locality: Puerto Madryn (43º14'S, 65º02'W), Chubut province Specimens in collections: MML (accession numbers not provided)V References: Berón-Vera et al. (2008) 2. Information on the developmental stage of the acanthocephalans is not provided in the published record. Anisakis simplex (Rudolphi, 1809) s.l. 3 Host: Delphinus delphis Linnaeus Site in host: forestomach Locality: northern Patagonia (39º–42ºS, 60º–62ºW) Specimens in collections: USNPC (99622)V References: Berón-Vera et al. (2007) Host: Lagenorhynchus cruciger (Quoy & Gaimard) Site in host: stomach Locality: Playa Unión (43º20'S, 65º00'W), Rawson, and Playa Paraná (42º49'S, 64º53'W), Puerto Madryn, Chubut province References: Fernández et al. (2003) Host: Lagenorhynchus obscurus (Gray) Site in host: forestomach, main stomach Locality: Claromecó (38º52'S, 60º05'W) and Necochea (38º27'S, 58º50'W), Buenos Aires province Specimens in collections: BMNH ... : Published as part of Hernández-Orts, Jesús S., Viola, M. Natalia Paso, García, Néstor A., Crespo, Enrique A., González, Raúl, García-Varela, Martín & Kuchta, Roman, 2015, A checklist of the helminth parasites of marine mammals from Argentina, pp. 301-334 in Zootaxa 3936 (3) on pages 308-310, DOI: 10.11646/zootaxa.3936.3.1, http://zenodo.org/record/236696 ...